THU0188 Evaluation of Single-dose and Steady-State Pharmacokinetics, Bioavailability and Tolerability of the Modified Release Formulation of Tofacitinib vs the Immediate Release Formulation of Tofacitinib in Healthy Volunteers. (9th June 2015) - Lamba, M.; Wang, R.; Fletcher, T.; Alvey, C.; Kushner, J.; Stock, T.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). An immediate-release (IR) tofacitinib formulation, dosed twice daily (BID), has been assessed in patients with RA. A modified-release (MR) formulation at 11 mg dose strength to provide once daily (QD) dosing equivalent to IR 5 mg BID has been developed to provide an additional and convenient dosing option. Objectives: To characterise the pharmacokinetics (PK) following single- and multiple-dose administration, assess the bioavailability and tolerability of the tofacitinib MR 11 mg QD proposed commercial formulation, and compare to that of the tofacitinib IR 5 mg BID commercial formulation. Methods: This was a Phase 1, randomised, open-label, crossover study in healthy volunteers (HV). HV were randomised to 1 of 2 treatment sequences each consisting of 2 periods, each including a single-dose and multiple-dose phase. In each period, HV received: a single-dose of tofacitinib MR 11 mg on Day 1, followed by tofacitinib MR 11 mg QD from Days 3-7; or 2 doses of tofacitinib IR 5 mg (separated by ∼12h) on Day 1, followed by tofacitinib IR 5 mg BID from Days 3-7. PK parameters were calculated using non-compartmental analyses. A mixed-effects model was used to generate adjusted geometric mean ratios (MR/IR) and 90% confidence intervals (CIs) for both total and peak exposure. For the IR treatment, peak exposure following the first of the 2 daily doses was used as the reference vs the MR treatment. Results: All 24 HV treated with tofacitinib were analysed for PK concentrations and safety. On Day 1 (single-dose phase), tofacitinib maximal plasma concentration (Cmax ) was equivalent for MR and IR. Median (range) time to tofacitinib Cmax (Tmax ) for MR was 4.0h (3.0-4.0h) vs 0.5h (0.5-1.0h) for IR. Mean (±standard deviation) terminal half-life was 5.9h (±1.8h) for MR and 3.2h (±0.8h) for IR. Total plasma tofacitinib exposure (area under curve [AUC] from time 0-infinity) was equivalent for MR and IR (ratio: 103.92% [90% CI: 98.81%, 109.28%]; Table ). On Day 7 (multiple-dose phase), steady-state Cmax was also equivalent for MR and IR. Ratios for minimum plasma (Cmin ) and trough (Ctrough ) concentrations were 70.64% (90% CI: 59.01%, 84.56%) and 73.54% (90% CI: 57.71%, 93.70%), respectively. Tofacitinib exposure (AUC for time 0-24h) was equivalent for MR and IR (ratio: 101.94% [90% CI: 97.79%, 106.27%]). Minimal accumulation of systemic exposures was observed for both MR and IR. 18 HV reported 39 adverse events (AEs). Most AEs were mild. There were no serious AEs, severe AEs or deaths. One HV permanently discontinued during tofacitinib IR treatment (unrelated; fungal skin infection). Types of AEs were generally similar between the formulations. Conclusions: In HV, tofacitinib MR demonstrated equivalence of AUC and Cmax following both single- and multiple-dose administration vs the IR formulation. Cmin was 29% lower for MR vs IR. Safety profiles for MR and IR formulations were generally comparable. Based on the similarity of PK exposure parameters, the safety and efficacy of MR and IR formulations are expected to be consistent. Acknowledgements: Study sponsored by Pfizer Inc. Editorial support was provided by AM Reid, PhD, of CMC, and funded by Pfizer Inc. Disclosure of Interest: M. Lamba Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Fletcher Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Alvey Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Kushner Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Stock Shareholder of: Pfizer Inc, Employee of: Pfizer Inc